Fast, interleaved, Look‐Locker–based T1 mapping with a variable averaging approach: Towards temperature mapping at low magnetic field. (27th September 2022) - Fiorito, Marco; Yushchenko, Maksym; Cicolari, Davide; Sarracanie, Mathieu; Salameh, Najat
Abstract : Proton resonance frequency shift (PRFS) is currently the gold standard method for magnetic resonance thermometry. However, the linearity between the temperature‐dependent phase accumulation and the static magnetic field B0 confines its use to rather high‐field scanners. Applications such as thermal therapies could naturally benefit from lower field MRI settings through leveraging increased accessibility, a lower physical and economical footprint, and further consideration of the technical challenges associated with the integration of heating systems into conventional clinical scanners. T 1 ‐based thermometry has been proposed as an alternative to the gold standard; however, because of longer acquisition times, it has found clinical use solely with adipose tissue where PRFS fails. At low field, the enhanced T 1 dispersion, combined with reduced relaxation times, make T 1 mapping an appealing candidate. Here, an interleaved Look‐Locker–based T 1 mapping sequence was proposed for temperature quantification at 0.1 T. A variable averaging scheme was introduced, to maximize the signal‐to‐noise ratio throughout T 1 recovery. In calibrated samples, an average T 1 accuracy of 85% ± 4% was achieved in 10 min, compared with the 77% ± 7% obtained using a standard averaging scheme. Temperature maps between 29.0 and 41.7°C were eventually reconstructed, with a precision of 3.0 ± 1.1°C and an accuracy of 1.5 ± 1.0°C. Accounting for longer thermal treatments and less strict temperature constraints, applications such as MR‐guided mild hyperthermia treatments at low field could be envisioned. Abstract : Through the proposed Look‐Locker–based T 1 mapping sequence, temperature maps of homogeneous doped‐water solutions at 0.1 T could be obtained in 10 min. The use of a variable averaging scheme enhanced T 1 estimation accuracy, leading to a temperature precision of 3.0 ± 1.1°C and an accuracy of 1.5 ± 1.0°C. Given the prolonged thermal treatments and the less strict temperature constraints, applications in MR‐guided hyperthermia treatments at low field could be envisioned.